Plan for the worst - Taylor, Jodi (Taylor, Jodi. Chronicles of St. Mary's, 2020)
"You know what they say - hope for the best, but plan for the worst. Max is quite accustomed to everything going wrong. She's St Mary's, after all. Disaster is her default state. But with her family reunited and a jump to Bronze Age Crete in the works, life is getting back to normal. Well, normal for St Mary's. And then, following one fateful night at the Tower of London, everything Max thought she knew comes crashing down around her. Too late for plans. The worst has happened. And who can Max trust now?"--Publisher.